IMPLEMENTASI ZAKAT ASN DI KUALA BARU ACEH - Khairuddin Khairuddin (Institut Agama Islam Negeri Batusangkar, 2021)
Zakat is one of the pillars of Islam that must be fulfilled for Muslims who have reached their haul and nisab. The types of assets that must be paid for zakat continue to grow from only five types, namely zakat, gold, silver, agriculture, trade, livestock, and rikaz, while nowadays there are more professions that generate a lot of money, including income from State Civil Apparatus (ASN). Given the large amount of income of an ASN, it is necessary to study the implementation and nisab of ASN zakat. Therefore, this study will discuss how the implementation of ASN Zakat and what the nisab is so that someone pays zakat and what percentage must be issued in Kuala Baru District, Aceh Singkil Regency. This study uses a descriptive qualitative method. The results of the discussion found that the people of Gunung Meriah District issued their zakat at the time of class IIIc and deducted it when they received their salary.